Description of The Event Rate of Controlled and Uncontrolled Hypertension Patients at Malingping Public Health Center (Puskesmas) - Mega Martin (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
The prevalence of hypertension in the world in 2000 according to WHO worldwide there were 972 million people or 26.4% of the earth's inhabitants experienced hypertension. Of the 972 million people with hypertension, 333 million are in developed countries and the remaining 63 million are in developing countries, including Indonesia. Knowing the description of the incidence of controlled and uncontrolled hypertension at the Malingping Health Center in 2021. Descriptive research design. Samples were taken using the purposive sampling technique, namely 119 patients who came for treatment at the Malingping Health Center. The results were analyzed univariately. Based on the results of the study, it can be seen from 106 respondents who were not controlled (81.1%), while those who were controlled were 13 respondents (10.9%). Age of hypertensive patients included in the groupage > 60 years as many as 62 samples (52.1%). The sex of the patients was mostly female, namely 88 samples (73.9%). The incidence of hypertension sufferers in the working area of ​​Malingping Health Center is still uncontrolled, in the age group > 60 years and female.